Effect of substrate concentration on lactic acid production using thermophilic lactic acid bacteria - Riana, Awang Saman (Universiti Malaysia Sarawak (UNIMAS), 2015)
The effect of glucose concentration in lactic acid (LA) production using thermophilic lactic acid bacteria (LAB) was investigated in this study. The aim was to investigate if the LAB could produce a high concentration of lactic acid (LA). Three different concentration of glucose were used in this work; 100 gil, 110 gil, and 120 gil. Batch fermentation was carried out in a 3 L bioreactor, with automatic titration of 10 M NaOH to control the pH 6.8, a temperature set at 45 °e, and an agitation rate of 100 rpm. The results showed that the thermophilic LAB was able to produce a high concentration of LA. Using initial concentration of] 20 gil of glucose has produced the highest LA production rate, In this case, LA produced was 112,6 gil and the specific production of LA per gram of cell was 32.45 gig h even though the volumetric production rate was low The specific LA production is the best reported for LA fermentation, However, the optimum glucose concentration that is suitable for LA production is ] 10 gil. Under this condition, the LAB produced a volumetric productivity and biomass concentration yield of5,12 gil h